2021
DOI: 10.1111/nan.12770
|View full text |Cite
|
Sign up to set email alerts
|

Image‐based deep learning reveals the responses of human motor neurons to stress and VCP‐related ALS

Abstract: Aims Although morphological attributes of cells and their substructures are recognised readouts of physiological or pathophysiological states, these have been relatively understudied in amyotrophic lateral sclerosis (ALS) research. Methods In this study, we integrate multichannel fluorescence high‐content microscopy data with deep learning imaging methods to reveal—directly from unsegmented images—novel neurite‐associated morphological perturbations associated with (ALS‐causing) VCP‐mutant human motor neurons … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…This may be attributed to weak signal that is diminished within the noise. Despite these limitations, previous work has demonstrated that ML classification can predict FALS origin in a small number of VCP mutant lines (Verzat et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This may be attributed to weak signal that is diminished within the noise. Despite these limitations, previous work has demonstrated that ML classification can predict FALS origin in a small number of VCP mutant lines (Verzat et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…While there are image-based algorithms and ML tools that enable neuronal segmentation, cell tracing, and identification of neurons, single neuron analyses remain difficult [4][5][6][7][8][9] . aNNs make an ideal choice to overcome limitations in the existing tools and have been implemented in similar contexts [10][11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%